2018
DOI: 10.4048/jbc.2018.21.2.227
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine Encapsulated Papillary Carcinoma of the Breast: The First Reported Case with an Infiltrative Component

Abstract: Apocrine encapsulated papillary carcinoma (EPC) of the breast is a rare neoplasm, and only 10 cases have been reported in the literature to date. Although EPC by definition lacks a peripheral myoepithelial layer, all previously published apocrine EPC cases were clinically indolent and lacked a conventional invasive component. Herein, we report the 11th case of apocrine EPC, which had a conventional invasive carcinoma component and provides evidence of the malignant potential of this entity. We postulate that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The 4 th and 5 th editions discuss these tumors under the heading of “ Carcinomas with apocrine differentiation ”, recognizing that several histological types may show apocrine morphology and immunophenotype: those listed beside IBC-NST include invasive micropapillary , lobular and mucinous carcinomas . Furthermore, encapsulated papillary carcinoma of apocrine differentiation has also been reported 45 , 46 . The 5 th edition defines apocrine differentiation by light microscopic morphology as cells with distinct cell borders, abundant granular eosinophilic or vacuolated cytoplasm, large round to oval nuclei and prominent nucleoli and a GCDFP-15+, ER- PR- AR+ immunophenotype 5 .…”
Section: The Classificationsmentioning
confidence: 97%
“…The 4 th and 5 th editions discuss these tumors under the heading of “ Carcinomas with apocrine differentiation ”, recognizing that several histological types may show apocrine morphology and immunophenotype: those listed beside IBC-NST include invasive micropapillary , lobular and mucinous carcinomas . Furthermore, encapsulated papillary carcinoma of apocrine differentiation has also been reported 45 , 46 . The 5 th edition defines apocrine differentiation by light microscopic morphology as cells with distinct cell borders, abundant granular eosinophilic or vacuolated cytoplasm, large round to oval nuclei and prominent nucleoli and a GCDFP-15+, ER- PR- AR+ immunophenotype 5 .…”
Section: The Classificationsmentioning
confidence: 97%
“…Further single case studies have observed similar morphological and IHC findings including AR positivity. Kovari et al recently reported the first case of apocrine EPC with accompanying invasive carcinoma, also showing apocrine morphology [40]. Where clinical follow-up is available, all patients with reported apocrine EPC remain well with no evidence of recurrence.…”
Section: Encapsulated Apocrine Papillary Carcinomamentioning
confidence: 98%
“…8 In the previous case report of the apocrine encapsulated papillary carcinoma with frank invasion, the biopsy specimen contained an invasive component. 8 Meanwhile, in our case, the biopsy specimen showed the same findings of the encapsulated papillary carcinoma component but without definitive invasion. Biopsy sites should be carefully determined using imaging findings because the location of the biopsy needle greatly influences diagnosis in such cases.…”
Section: Discussionmentioning
confidence: 97%
“…1,10,11 On the other hand, a previous report showed that patients with apocrine encapsulated papillary carcinoma without invasion survived without recurrence even when they were not treated with systemic therapy. 5,8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation